STRATEGI ADAPTASI NELAYAN DI KAWASAN DANAU SEMAYANG KABUPATEN KUTAI KARTANEGARA - Sulistianto, Erwan; ., Erwiantono (Jurnal Harpodon Borneo, 2015)
The purpose of this research was to analyze the socio-economic strategy that has been carried out by the fisheries community in the area of SemayangLake in order to response the changes in fishery resources which has been their source of livelihood. The research was conducted by survey method which are conducting an interviews based on questionnaires and direct observations in the field. Data collected in the form of primary data by the survey methods and secondary data by reviewing publicationsthat is connected to the purpose of research. The results showed that the strategiescarried out by the fishing community in the area of SemayangLake were : 1) implementing multiple livelihoods pattern in households of fishermen to overcome economic difficulties by involving household members worked in fishing effort. On the next phase, the multiplelivelihoods strategy was developed into diversification of other types of fishing bussinesshold by families of fishermen. 2) Establishing and expanding the social network of fishing communities, where social networks are formed vertically (forming network between fishermen and traders / capital owners / Ponggawa) and horizontallly (forming network among fishermen). 3) Establishing a social institution on fisheries communities that guidingand controlling the thesustainable utilization of fisheries resources and preserving the integrity of the fisheries society (as social glue). Keywords : Semayang Lake, socio-economic strategy, Fishermen